Pengaruh pajak daerah, retribusi daerah, dana perimbangan, SiLPA terhadap alokasi belanja daerah pada Kabupaten/Kota Provinsi Sumatera Selatan Tahun 2017-2019 - Marbun, Susiana; Putri Manalu, Erna; Nelsari Malau, Yois (Jurnal Paradigma Ekonomika, 2022)
This research examines the influence of Regional Taxes, Regional Levies, Balance Funds, and SiLPA on Regional Expenditure Allocations in the Regency/City of South Sumatra Province in 2017-2019. This presentation uses a quantitative descriptive type, with the number of samples being 17 districts/cities. In the choice of models, used saturated sampling technique. Retrieval data sources using documentation techniques whose data is taken through the website www.bpssumsel.go.id. In the coefficient test, the result obtained Adjusted R2 worth 0.942, meaning 94.2%, and the rest of the other independent that have not yet been studied in this regard presentation are 5,8%. The discussion obtained that regional taxes, regional levies, and balancing funds influence, but SiLPA does not affect regional expenditure allocation. Provincial taxes, regional levies, balancing funds, and SiLPA of the whole are stated to impact the regional expenditure allocation. Â